Perspectives in Business Informatics Research 9th International Conference, BIR 2010, Rostock, Germany, September 29--October 1, 2010, Proceedings - Forbrig, Peter; Günther, Horst (Lecture Notes in Business Information Processing, 2010)
The conference series BIR (Business Informatics Research) was established 10 years ago in Rostock as an initiative of researchers from Swedish and German universities. The objective was to create a global forum where researchers in business informatics, seniors as well as juniors, could meet, collaborate and - change ideas. Over the years BIR has matured into a series of international conferences, typically organized in the Baltic Sea region, including Norway and Iceland. A steering committee ensures the high quality of the BIR proceedings. We are very proud that this year an international and very well known editor has agreed to publish selected papers of the conference. The interest in the conference in terms of submissions and participation has steadily increased over the years. This year, we received 53 contributions among which 14 submissions were accepted as long papers and 4 as short papers. A few additional contributions were invited for presentation at the conference. The selection was carefully carried out by an International Program C- mittee. The result is a set of interesting and stimulating papers that address important issues such as knowledge management, ontologies, models, work?ow speci?cations, data bases and OLAP. The conference was opened by an invited technical talk by Dr. Klaus BrunnsteinfromTheUniversityofHamburgwhodiscussedthetopic"TheInf- mation Society on the Way to Web 3.0: Perspectives, Opportunities and Risks", which is challenging for all of us.